2012
DOI: 10.3390/ijms13044623
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Bismuth Tellurite Based Glass

Abstract: A series of binary tellurite based glasses (Bi2O3)x (TeO2)100−x was prepared by melt quenching method. The density, molar volume and refractive index increase when bismuth ions Bi3+ increase, this is due to the increased polarization of the ions Bi3+ and the enhanced formation of non-bridging oxygen (NBO). The Fourier transform infrared spectroscopy (FTIR) results show the bonding of the glass sample and the optical band gap, Eopt decreases while the refractive index increases when the ion Bi3+ content increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(30 citation statements)
references
References 29 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…The direct and indirect energy band gaps obtained for the TSW glasses are comparable to many other tellurite based glasses [31]. From Amorphous materials, such as glasses contain a band tailing in the forbidden energy band gap.…”
Section: Optical Band Gap and Urbach Energymentioning
confidence: 69%
“…The direct and indirect energy band gaps obtained for the TSW glasses are comparable to many other tellurite based glasses [31]. From Amorphous materials, such as glasses contain a band tailing in the forbidden energy band gap.…”
Section: Optical Band Gap and Urbach Energymentioning
confidence: 69%
“…Hence, the substitution of Gd 3+ ions (1.79 Å) which have higher atomic radius than the atomic radius of tellurite atom (1.6 Å) and boron atom (0.98 Å) into the network enhances the increase in refractive index with increasing the rare earth ion concentration. It is due to high polarization value of these ions resulting from increasing of cation size [28,29]. The refractive index obtained in this work is higher than the refractive index reported for calcium borotellurite glass system, which is desirable for fiber optic design and waveguide applications [30].…”
Section: Density and Molar Volumementioning
confidence: 76%
“…Optical studycan be auseful toolnot only to investigate optically-induced electronic transitions but also to provide useful information on energy gap and band structure, which can be linked to glass networkmodification [44,52]. Aprevious studyonternary10 R O-40ZnO-50B 2 O 3 glass containing af ixed composition of alkaline earth oxides ( R =Mg, Ca, Sr and Ba) showed that optical energy gap ( E opt )d ecreases; at the same time, Urbach energy ( E u )and refractive index ( n )i ncrease withg radualr eplacement of alkaline earth oxide in glass systemsi nt he order of MgO to BaO [53].…”
Section: Introductionmentioning
confidence: 99%